Teachers’ classroom control through decision-making: A case study in a private secondary school in Selangor / Kenny Cheah Soon Lee - Cheah, Kenny Soon Lee (2015)
This case study investigated on teachers’ classroom control strategies and decision-making simultaneously. In the private secondary school, teachers were strongly prohibited from disciplining students physically to avoid potential litigation threats and complaints from parents as stakeholders. From researcher’s activity as a participant observer, the Head of Discipline (HOD) reported of receiving discipline cases that were considered trivial and unnecessary that could have been rectified at teachers’ personal level. Under such restrictions and circumstance, teachers were investigated on their alternative forms of disciplining and their personal involvement in decision-making. Thus, fifteen teachers including the Head of Discipline (HOD) were chosen through purposive sampling to share on their experience in three areas: (a) as decision-makers; (b) their decision-making process; and (c) their unfavorable conditions and obstacle to personal decision-making. An open-ended Decision-making questionnaire was used together with a voice-recorded interview to collect information on their strategies, process and obstacles to personal decision-making. In addition, the pupil control ideology (PCI) form and Teachers’ Sense of Efficacy Scale (TSES) were also used to describe their personal profiles on their styles and confidence in classroom control. Data were subsequently transcribed, codded and analyzed sequentially in the three areas. As a result, teachers’ classroom control strategies were categorized into self-directed, student-directed, situation-directed and organizational-directed strategies. Each strategy contained tactics to educate, correct and prevent student from causing discipline problems. Secondly, respondents’ processes of decision-making were described as a pattern that progressed from personal involvement, to collaboration and finally transfer in relation to the perceived level of seriousness in the discipline problem. In addition, respondents were described in their extent of personal involvement through their frequencies of transfers, their PCI/TSES scores, perceptions on problem-seriousness, and their personal interventions prior to transfer. Within personal intervention, respondents were able to gather evidence(s), trace discipline problems to cause(s) and differentiate the type(s) of discipline problems. Thirdly, respondents’ highlighted a list of unfavorable conditions and six obstacles to personal decision-making; (a) Standard Operating Procedures (SOPs); (b) negative work culture; (c) social-cultural differences; (d) negative teacher-student relationship; (e) managing students with Learning Disabilities (LD); and (f) parental involvement. Eventually, the researcher compiled a list of suggestions from respondents to improve personal involvement and teachers’ collaborations in organizational decision-making. As an implication of research, this case study has contributed a contextual evidence for the researched organization to understand respondents’ behaviors as classroom leaders and their dilemmas in managing classroom discipline problems. Additionally, the Head of Discipline could rely on data findings to assist respondents in improving their personal decision-making on discipline problems that do not require transfer. Due to the limitations of a case study, no generalization can be made on the findings of this case study to reflect the whole population of teachers in the organization. As a concluding recommendation, respondents who portrayed different styles and levels of confidence through the analyses of the TSES and the PCI form could be paired for peer coaching, or conduct action research individually as a form of organizational learning.